2022
DOI: 10.1021/acs.iecr.2c02812
|View full text |Cite
|
Sign up to set email alerts
|

Shaft Power Consumption of Stirred Tank with Particles: From the Perspective of Pseudoshearing Thinning Rheological Property of Particles

Abstract: Accurately determining the shaft power consumption is important in the design and scale-up of stirred tanks with particles. Firstly, the apparent viscosity of the stirring particles is proposed. The effects of impeller type, agitation speed, and particle filling level on the apparent viscosity of the stirring particles are experimentally studied with various particles. It was found that larger particles, a greater friction coefficient between particles, and a higher particle filling level all result in a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The temperature rise corresponds to the generated heat, which is related to the amount of power consumed and subsequently dissipated by the granular medium during agitation. Others also showed such observations [7,8,40], confirming that the torque exerted by the blades to the granular medium increases with blade size, fill ratio, rotating speed and particle size.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The temperature rise corresponds to the generated heat, which is related to the amount of power consumed and subsequently dissipated by the granular medium during agitation. Others also showed such observations [7,8,40], confirming that the torque exerted by the blades to the granular medium increases with blade size, fill ratio, rotating speed and particle size.…”
Section: Discussionmentioning
confidence: 72%
“…When particles are filled above the blade span, the pressure distribution within the granular medium becomes approximately hydrostatic [40]. Therefore, at higher fill ratios, greater pressure is acting on the particles from those above the blade, leading to a greater resistance for the blade to overcome.…”
Section: Influence Of Fill Ratiomentioning
confidence: 99%
“…The temperature rise corresponds to the generated heat, related to the amount of power consumed and dissipated by the granular medium during agitation. Others also showed such observations, 7,8,40 confirming that the torque exerted by the blades to the granular medium increases with blade size, fill ratio, rotating speed and particle size. However, further investigation is required to understand better the heat generation behavior of granular materials, particularly in quantifying the generated heat and other forms of energy.…”
Section: Discussionmentioning
confidence: 74%
“…When particles are filled above the blade span, the pressure distribution within the granular medium becomes approximately hydrostatic. 40 Therefore, at higher fill ratios, greater pressure is acting on the particles from those above the blade, leading to a greater resistance for the blade to overcome. This was also confirmed by Boonkanokwong et al, 8 who showed that the impeller torque was greater for higher fill ratios.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation